Spectrophotometric Method Developed For The Estimation Of Flucloxacilin In Bulk And Dosage Form Using UV-VIS Spectrophotometric Method - SUDDHASATTYA DEY,; RATNAKAR CH.,; S. VAITHIYANATHAN,; HIMANSU BHUSAN SAMAL,; Y.VIKRAM REDDY,; BALA KRISHNA,; Y. ANIL REDDY,; G. NAVIN KUMAR,; SUBHASIS MOHAPATRA, (International Journal of Pharma and Bio Sciences, 2010)
The present study describes a simple, accurate, precise and cost effective UV-VIS Spectrophotometric method for the estimation of FLUCLOXACILLIN, is a penicillin beta-lactam antibiotic, in bulk and pharmaceutical dosage form. The solvent used was double distilled water and the λmax or the absorption maxima of the drug was found to be 219nm. A linear response was observed in the range of 2-10µg/ml with a regression coefficient of 0.998. The method was then validated for different parameters as per the ICH 2(International Conference for Harmonization) guidelines. This method can be used for the determination of FLUCLOXACILLIN in quality control of formulation without interference of the excipients.